A comparative review of electrical energy storage systems for better sustainability - Nikolaidis, Pavlos; Poullikkas, Andreas (Journal of power technologies, 2017)
The accelerated growth of the energy economy is still highly dependent on finite fossil fuel reserves. Modern power systems could not exist without the many forms of electricity storage that can be integrated at different levels of the power chain. This work contains a review of the most important applications in which storage provides electricity-market opportunities along with other benefits such as arbitrage, balancing and reserve power sources, voltage and frequency control, investment deferral, cost management and load shaping and levelling. Using a 5 function normalization technique a comparative assessment of 19 electrical energy storage (EES) technologies, based on their technical and operational characteristics, is carried out and the technology-application pairs identified across the power chain are presented. In terms of safety and simplicity, Pbacid and Li-ion systems are viable options for small-scale residential applications, while advanced Pb-acid and molten-salt batteries are suited to medium-to-large scale applications including commercial and industrial consumers. In addition to their expected use in the transportation sector in the coming years, regenerative fuel cells and flow batteries have intriguing potential to offer in stationary applications once they are mature for commercialization. For large-scale/energy-management applications, pumped hydro is the most reliable energy storage option (over compressed-air alternatives) whereas flywheels, supercapacitors and superconducting magnetic energy storage (SMES) are still focused on power-based applications. As different parts in the power system involve different stakeholders and services, each technology with its own benefits and weaknesses requires research and development in order to emerge over others and contribute to more effective energy production in the future.